Coût direct et géographie des ralentissements subis par les transports publics bruxellois - Frédéric Dobruszkes; Yves Fourneau (Brussels Studies)
Automobile traffic causes a decrease in the surface mass transport’s effectiveness in Brussels as in other cities. In economic terms, this corresponds to lower returns and productivity for the operator. This article documents economically – in terms of direct costs – and geographically how road traffic slows down the region’s urban buses and trams. Such a computation appears to be unprecedented, although it offers a different way to state the problem of financing public transport and of analysing the conflict between automobile transport and mass transport. The aggregation of spatially and temporally fine data enables the authors to conclude that at least 18% of the supply’s production cost serves only to offset these running delays. Moreover, a detailed map of service along the various routes that allows for the frequencies of the vehicles’ runs reveals the trouble spots where urgent action is necessary and shows that creating exclusive rights of way is not enough.